2019
DOI: 10.1002/chem.201903224
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Packing and Solid‐State Photophysical Properties of 1,3,6,8‐Tetraalkylpyrenes

Abstract: The relationship between the photophysical properties and molecular orientation of 1,3,6,8‐tetraalkylpyrenes in the solid state is described herein. The introduction of alkyl groups with different chain structures (in terms of length and branching) did not affect the photophysical properties in solution, but significantly shifted the emission wavelengths and fluorescence quantum yields in the solid state for some samples. Pyrenes bearing ethyl, isobutyl, or neopentyl groups at the 1‐, 3‐, 6‐, and 8‐positions s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…These bathochromic shifts are due to increasing HOMO energy levels from CÀ H/CÀ C σ-π hyper conjugation between the Py chromophore and alkyl groups. [17,18] Additionally, the solid-state fluorescence profiles of the co-crystals were essentially the same as a dilute solution of Py derivatives ( Table 1 and Figures S2-S5). These results, along with the interleaved faceto-face packing mode of these co-crystals (vide infra), indicate that the intercalated OFN efficiently separates the Py cores to avoid excimer formation in the co-crystal.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…These bathochromic shifts are due to increasing HOMO energy levels from CÀ H/CÀ C σ-π hyper conjugation between the Py chromophore and alkyl groups. [17,18] Additionally, the solid-state fluorescence profiles of the co-crystals were essentially the same as a dilute solution of Py derivatives ( Table 1 and Figures S2-S5). These results, along with the interleaved faceto-face packing mode of these co-crystals (vide infra), indicate that the intercalated OFN efficiently separates the Py cores to avoid excimer formation in the co-crystal.…”
Section: Resultsmentioning
confidence: 82%
“…When Pen 4 Py was recrystallized from MeOH and CHCl 3 , two polymorphic crystals were obtained, which exhibited emission at 420 nm along with shoulders at 440 and 470 nm. [17] Although the contribution of the excimer was small in these crystalline samples, an excimer emission centered at 470 nm was mainly observed in a less organized drop-cast sample. These emission profiles of pure Pen 4 Py in the solid state suggested that the introduction of pentyl groups at the 1-, 3-, 6-, and 8-positions suppresses the excimer formation in the crystal, but unregulated molecular orientation leads to excimer formation in the solid state as observed in the drop-cast sample ( Figure S9).…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations